Results of genetic analysis of 11 341 participants enrolled in the My Life, Our Future hemophilia genotyping initiative in the United States. (17th July 2022) - Johnsen, Jill M.; Fletcher, Shelley N.; Dove, Angela; McCracken, Haley; Martin, Beth K.; Kircher, Martin; Josephson, Neil C.; Shendure, Jay; Ruuska, Sarah E.; Valentino, Leonard A.; Pierce, Glenn F.; Watson, Crystal; et al.
Abstract: Background: Hemophilia A (HA) and hemophilia B (HB) are rare inherited bleeding disorders. Although causative genetic variants are clinically relevant, in 2012 only 20% of US patients had been genotyped. Objectives: My Life, Our Future (MLOF) was a multisector cross‐sectional US initiative to improve our understanding of hemophilia through widespread genotyping. Methods: Subjects and potential genetic carriers were enrolled at US hemophilia treatment centers (HTCs). Bloodworks performed genotyping and returned results to providers. Clinical data were abstracted from the American Thrombosis and Hemostasis Network dataset. Community education was provided by the National Hemophilia Foundation. Results: From 2013 to 2017, 107 HTCs enrolled 11 341 subjects (68.8% male, 31.2% female) for testing for HA ( n = 8976), HB ( n = 2358), HA/HB ( n = 3), and hemophilia not otherwise specified ( n = 4). Variants were detected in most male patients (98.2%% HA, 98.1% HB). 1914 unique variants were found (1482 F8, 431 F9 ); 744 were novel (610 F8, 134 F9 ). Inhibitor data were available for 6986 subjects (5583 HA; 1403 HB). In severe HA, genotypes with the highest inhibitor rates were large deletions (77/80), complex intron 22 inversions (9/17), and no variant found (7/14). In severe HB, the highest rates were large deletions (24/42). Inhibitors were reported in 27.3% of Black versus 16.2% of White patients. Conclusions: The findings of MLOF are reported, the largest hemophilia genotyping project performed to date. The results support the need for comprehensive genetic approaches in hemophilia. This effort has contributed significantly towards better understanding variation in the F8 and F9 genes in hemophilia and risks of inhibitor formation.